FAKTOR-FAKTOR PENGAMBILAN KEPUTUSAN DALAM MEMILIH DESTINASI WISATA - Yulis Wulandari (Jurnal Pendidikan Nusantara, 2021)
The tourism sector is increasing with intense competition, so tourism destinations tend to experience an increase and decrease in tourists. Research studies are focused on tourist decision-making: exploring the criteria for destination choice due to several factors. Especially the most dominant factor has a significant influence on tourists' decisions in choosing destination criteria. This factor is essential for the tourism sector to be developed in the future so that it is no less competitive with the current intense competition. From several similar articles used as references, there are four factors that influence tourist decisions: comfort, climatic conditions, extraordinary objects, and affordable tourist facilities.